2002
DOI: 10.1542/peds.110.2.254
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Adverse Drug Reactions on a Pediatric Ward: A Strategy for Early and Detailed Detection

Abstract: The detection rate of ADRs would almost be doubled by a computerized monitoring system analyzing laboratory data. Implementation of a computer monitor system that automatically generates laboratory signals may help to identify ADRs in children, and to reduce morbidity and hospital stay, as well as costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
2
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 14 publications
3
45
2
4
Order By: Relevance
“…Although we combined interview with parents with chart review, which detects a higher percentage of ADRs than other methods [31], we found a lower rate of ADRs (0.9%) with respect to other studies.…”
Section: Discussioncontrasting
confidence: 74%
“…Although we combined interview with parents with chart review, which detects a higher percentage of ADRs than other methods [31], we found a lower rate of ADRs (0.9%) with respect to other studies.…”
Section: Discussioncontrasting
confidence: 74%
“…The overall incidence (1.8%) of ADRs in this study is comparable with the 1.1% previously reported in Nigeria. 3 However, when this rate is compared with results (2.1% to 9.5%) from developed countries, 6,7 ADRs are still grossly underreported in Nigeria.…”
Section: Discussionmentioning
confidence: 81%
“…The majority of studies were described as being performed in a general paediatric unit or ward (n = 24), 32 118 of which included general medicine. Three studies 75,165,166 included children on an isolation ward. One study was performed using an integrated primary care information database.…”
Section: Description Of Studiesmentioning
confidence: 99%